The charmed circle: identity in Utopia, unethical practices, and Augustine's two cities. (September 2022) - DeCook, Travis
Abstract : This article considers Utopia's unethical practices alongside The City of God 's understanding of the earthly polity's relationship to eschatology. In Augustine's view, within the earthly city every person could potentially become a friend of the heavenly city in time, and the existing political situation must always be rendered partial and incomplete against the telos of eternity. These convictions stand in conspicuous contrast with Utopia. The Utopian system is in important ways founded on institutionalized practices which not only exclude non-Utopians (or ex-Utopians), but also habituate them to vice. Examining Utopia alongside The City of God illuminates how this ethical problem in Utopia is not just a matter of individual practices or institutions, but rather derives from a more fundamental metaphysical and theological outlook. Not only is Utopia invested in a Utopian/non-Utopian distinction; more significantly, this distinction has a tacit eschatological role, since Utopian thinking implies that degradation of one's capacity for virtue decreases one's potential to be saved. Abstract : Cet article examine les pratiques utopiennes contraires à l'éthique en se basant sur la relation entre la politique terrestre et l'eschatologie exposée dans la Cité de Dieu . Selon Augustin, dans la cité terrestre, chacun pourrait potentiellement devenir un ami de la cité céleste avec le temps, et la situation politique existante doit toujours être comprise comme partielle et incomplète par rapport au telos de l'éternité. Ces convictions contrastent nettement avec l'Utopie. Le système utopien est fondé de manière importante sur des pratiques institutionnalisées qui, non seulement excluent les non-Utopiens (ou ex-Utopiens), mais aussi les habituent au vice. L'examen de l' Utopie aux côtés de la Cité de Dieu montre clairement comment ce problème éthique en Utopie n'est pas seulement une question de pratiques ou d'institutions individuelles, mais découle plutôt d'une perspective métaphysique et théologique plus fondamentale. L'Utopie n'est pas seulement investie dans une distinction utopien/non-Utopien: plus important encore, cette distinction a un rôle eschatologique tacite, puisque la pensée utopienne implique que la dégradation de l'aptitude à la vertu chez un individu diminue son potentiel de salut.